2020
DOI: 10.1007/s12170-020-00642-8
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Cardiovascular Risk in the Arab Gulf States

Abstract: Purpose of Review Rapid economic growth in the Gulf Cooperation Council (GCC) states over the last half-century has been associated with a rise in obesity and cardiovascular morbidity and mortality. In this review, we shed some light on the factors driving the obesity epidemic, promising interventions to overcome this public health crisis, and challenges precluding a successful public health impact. Recent Findings Overweight and obesity rates have nearly tripled in the GCC countries over the past four decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…Our large sample included both Saudi and non-Saudi populations and showed a wider extent of obesity prevalence (45% women vs. 31% men). Our ndings are also consistent with the Almajwal et al study that showed an increased risk of diabetes and hypertension among the Saudi population relative to their BMI [21,23].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our large sample included both Saudi and non-Saudi populations and showed a wider extent of obesity prevalence (45% women vs. 31% men). Our ndings are also consistent with the Almajwal et al study that showed an increased risk of diabetes and hypertension among the Saudi population relative to their BMI [21,23].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, several previous regional cross-sectional studies have indicated variations in obesity prevalence in the Kingdom [21,24,25]. Although these rates varied between regions due to limited sample size and differences in age groups, their ndings consistently align with our ndings on the higher obesity prevalence among women.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations